Conversion training of conventional to sharia cooperatives for regional leaders of 'Aisyiyah, Malang City - Tinuk Dwi Cahyani; Rahayu Hartini; Fadilla Muhammad Mahdi (Universitas Muhammadiyah Magelang, 2021)
Islamic Cooperation; Conversion; Training